Enabling High‐Performance NASICON‐Based Solid‐State Lithium Metal Batteries Towards Practical Conditions. (20th May 2021) - Paolella, Andrea; Liu, Xiang; Daali, Amine; Xu, Wenqian; Hwang, Inhui; Savoie, Sylvio; Girard, Gabriel; Nita, Alina Gheorghe; Perea, Alexis; Demers, Hendrix; Zhu, Wen; Guerfi, Abdelbast; et al.
Abstract: Solid‐state lithium metal batteries (SSLMBs) are promising next‐generation high‐energy rechargeable batteries. However, the practical energy densities of the reported SSLMBs have been significantly overstated due to the use of thick solid‐state electrolytes, thick lithium (Li) anodes, and thin cathodes. Here, a high‐performance NASICON‐based SSLMB using a thin (60 µm) Li1.5 Al0.5 Ge1.5 (PO4 )3 (LAGP) electrolyte, ultrathin (36 µm) Li metal, and high‐loading (8 mg cm −2 ) LiFePO4 (LFP) cathode is reported. The thin and dense LAGP electrolyte prepared by hot‐pressing exhibits a high Li ionic conductivity of 1 × 10 −3 S cm −1 at 80 °C. The assembled SSLMB can thus deliver an increased areal capacity of ≈1 mAh cm −2 at C/5 with a high capacity retention of ≈96% after 50 cycles under 80 °C. Furthermore, it is revealed by synchrotron X‐ray absorption spectroscopy and in situ high‐energy X‐ray diffraction that the side reactions between LAGP electrolyte and LFP cathode are significantly suppressed, while rational surface protection is required for Ni‐rich layered cathodes. This study provides valuable insights and guidelines for the development of high‐energy SSLMBs towards practical conditions. Abstract : A solid‐state lithium metal battery using an ultrathin Li metal anode, thin NASICON‐based solid‐state electrolytes, and thick LiFePO4 cathode towards practical application is developed. Moreover, this cell design significantly decreases the internal cell resistance and mitigates the parasitic reactions between the cathode and solid electrolytes, thus demonstrating excellent cycle stability and rate capability with high areal capacity.